Association of Spiritual Health and Quality of Life in the Hemodialysis Patients Admitted in Shahid Motahari Hospital in Jahrom, Iran (2016) - M Milan; F Nasimi; I Hafizi; M Ghorbanzadeh; Y Hosseini (Iran University of Medical Sciences, 2018)
Background & Aims: Impaired performance and poor quality of life may deteriorate the psychological health of the patients undergoing hemodialysis. Spiritual behaviors, especially bonding with God, could improve spiritual energy and create a positive attitude in these patients. The present study aimed to assess the association between spiritual wellbeing and quality of life in hemodialysis patients. Materials & Methods: This descriptive-analytical study was conducted on 82 hemodialysis patients in the Hemodialysis Center of Motahari Hospital in Jahrom, Iran in 2016. The subjects were selected via convenience sampling. Data were collected using the quality of life questionnaire for renal patients and the spiritual wellbeing scale by Paloutzian and Ellison. Data analysis was performed in SPSS version 20 using descriptive (mean and standard deviation) and inferential statistics (Pearson's correlation-coefficient). Results: Positive, significant correlations were observed between the dimensions of quality of life, including physical functioning (0.222), role impairment due to emotional problems (0.260), energy/fatigue (0.393), general health (0.394), and physical health (0.293), and domains of spiritual wellbeing. Conclusion: According to the results, it is critical to enhance spiritual wellbeing as an important influential factor in the quality of life of individuals. Paying attention to the key role of spiritual health in a country like Iran, where cultural values and religious beliefs prevail, could be beneficial in developing effective healthcare programs for hemodialysis patients.